2014
DOI: 10.1186/1471-2253-14-66
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high–flow oxygen therapy in patients with hypoxic respiratory failure: effect on functional and subjective respiratory parameters compared to conventional oxygen therapy and non-invasive ventilation (NIV)

Abstract: BackgroundAim of the study was to compare the short-term effects of oxygen therapy via a high-flow nasal cannula (HFNC) on functional and subjective respiratory parameters in patients with acute hypoxic respiratory failure in comparison to non-invasive ventilation (NIV) and standard treatment via a Venturi mask.MethodsFourteen patients with acute hypoxic respiratory failure were treated with HFNC (FiO2 0.6, gas flow 55 l/min), NIV (FiO2 0.6, PEEP 5 cm H2O Hg, tidal volume 6–8 ml/kg ideal body weight,) and Vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 24 publications
6
124
2
6
Order By: Relevance
“…32 An improvement in the Pao 2 :Fio 2 ratio was observed among patients receiving noninvasive ventilation compared with HFNC oxygen therapy, as has been reported previously. 38 This result may have been due to the higher positive end-expiratory pressure or higher mean airway pressure being applied during noninvasive ventilation. 39,40 We found no significant differences between HFNC oxygen therapy and the control groups in ICU mortality or length of ICU stay.…”
Section: Discussionmentioning
confidence: 94%
“…32 An improvement in the Pao 2 :Fio 2 ratio was observed among patients receiving noninvasive ventilation compared with HFNC oxygen therapy, as has been reported previously. 38 This result may have been due to the higher positive end-expiratory pressure or higher mean airway pressure being applied during noninvasive ventilation. 39,40 We found no significant differences between HFNC oxygen therapy and the control groups in ICU mortality or length of ICU stay.…”
Section: Discussionmentioning
confidence: 94%
“…An observational study by Lenglet et al 11 showed that HFNC decreased dyspnea scores compared with COT in subjects with acute respiratory failure presenting to an emergency department. Furthermore, Schwabbauer et al 12 found that HFNC significantly reduced dyspnea and improved comfort compared with noninvasive ventilation in subjects with hypoxemic respiratory failure. In addition, the subjects in the present study tolerated HFNC very well, and no serious adverse events occurred during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…7 In mild hypoxemic situations, although NIV produces better oxygenation, HFNC is subjectively better tolerated, and it can be considered as a reasonable alternative therapy. 8 However, we disagree with the use of HFNC in moderate or severe ARDS (P aO 2 / F IO 2 of Ͻ 200). ARDS is a clinical condition with high mortality.…”
Section: To the Editormentioning
confidence: 99%